High-performance environment-friendly coating and galvanized sheet prepared from high-performance environment-friendly coating

By adding graphene oxide nanosheets, boron nitride nanosheets and inorganic nanoparticles to the aqueous polyurethane coating, the shortcomings of water-based polyurethane coatings in terms of mechanical properties, water resistance, heat resistance and chemical stability are solved, and the preparation of high-performance environmentally friendly coatings is realized.

CN119684886AActive Publication Date: 2025-03-25淄博佳悦板业有限公司

Patent Information

Application Number
CN202510221807.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-03-25
Estimated Expiration
2045-02-27

AI Technical Summary

Technical Problem

The existing water-based polyurethane coatings are inferior to solvent-based polyurethane in terms of film formation curing time, mechanical properties, water resistance, heat resistance and chemical stability. At the same time, the dispersion and compatibility of nanomaterials in the polyurethane matrix are poor.

Method used

The aqueous polyurethane is modified by graphene oxide nanosheets, boron nitride nanosheets and inorganic nanoparticles. By adjusting the amount and particle size of each component, the dispersion of fillers is promoted, the formation of a dense structure is formed, and the hardness and stability of the coating are improved.

Benefits of technology

The preparation of high-performance environmentally friendly coatings has been realized. The coating has excellent mechanical properties, easy construction and weather resistance, and has broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure NWJ80RUTYWMUBHCEAPSU5LCGHF2X3VEDR6DKM9M5
    Figure NWJ80RUTYWMUBHCEAPSU5LCGHF2X3VEDR6DKM9M5
Patent Text Reader

Abstract

The invention relates to the technical field of coatings, in particular to a high-performance environment-friendly coating and a galvanized sheet prepared from the same. The high-performance environment-friendly coating is prepared from the following components in parts by weight: 120 to 150 parts of waterborne polyurethane dispersion liquid, 10 to 15 parts of graphene oxide nanosheets, 4 to 10 parts of boron nitride nanosheets, 2 to 6 parts of inorganic nanoparticles, 0.5 to 2 parts of anti-settling agent, 0.5 to 2 parts of defoaming agent, 0.2 to 2 parts of wetting dispersant and 50 to 100 parts of deionized water. By selecting inorganic nanoparticles with specific particle sizes, the inorganic nanoparticles can be dispersed between the boron nitride nanosheets and the graphene oxide nanosheets, the dispersion and lubrication effects similar to those of bearings are achieved, the isolation and shielding effects of the nanosheet material are improved, and the stability of the coating is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, and in particular to a high-performance environmentally friendly coating and a galvanized sheet prepared therefrom. Background Art

[0002] Galvanized sheet has excellent corrosion resistance and excellent processing and forming properties, and has been widely used in household appliances, automobiles and other industries. However, galvanized sheet will react chemically with water vapor, oxygen and other substances in a humid environment, causing corrosion on the coating surface. In order to ensure that the product does not rust during storage and transportation, the surface of the galvanized sheet generally needs to be passivated.

[0003] In order to eliminate the above problems, people coat a layer of thin film material on the surface of the galvanized sheet to reduce its surface energy, so that the coating has high mechanical properties while also having other properties such as corrosion resistance, alkali washing resistance, and blackening resistance.

[0004] Polyurethane is a type of polymer with typical carbamate functional groups, which are usually obtained by reacting polyisocyanates with hydroxyl components of polyethers, polyesters, hydroxy acrylics, and hydroxy alkyds under the conditions of some suitable additives. Polyurethane is widely used in life, medical treatment, industry, and even defense due to its excellent properties, such as good wear resistance, corrosion resistance, adhesion, chemical stability, and controllable soft and hard segments.

[0005] According to the different dispersion media, polyurethane can be divided into two categories: solvent-based polyurethane and water-based polyurethane. Water-based polyurethane is a new type of polyurethane system with water as the dispersion medium, also known as water-dispersed polyurethane, water-based polyurethane or water-based polyurethane. Since there is no or a small amount of organic solvent in the system, it can meet the increasingly stringent environmental protection requirements, and the harm to human health and pollution to the environment are relatively small. Although water-based polyurethane has the advantages of being environmentally friendly and environmentally friendly, it is still inferior to solvent-based polyurethane in terms of film-forming and curing time, mechanical properties, water resistance, heat resistance and chemical stability.

[0006] With the development of polyurethane, people pay more and more attention to the development of efficient and high-performance coatings. Conventional polyurethane can no longer meet the requirements due to its defects in performance and application. The modification of polyurethane has become one of the research hotspots in this field and has achieved rapid development. According to different modifiers, the modification of polyurethane is divided into structural modification and nanofiller modification.

[0007] Among them, nanomaterials have the characteristics of surface effect, small size effect, quantum size effect and macro quantum tunneling effect, thus showing unique acoustic, optical, electrical, magnetic, thermal and mechanical properties. Adding them to the polyurethane matrix can give a new superposition effect, significantly affecting the performance of the composite material with extremely low content. Nanomaterials can not only improve the comprehensive properties of traditional polyurethane such as electricity, heat and mechanics, but also improve its barrier properties. However, nanomaterials are small in size, have a large specific surface area and surface energy, and are easy to agglomerate. They cannot be well dispersed in the polyurethane matrix and cannot be well integrated with the polyurethane matrix. Therefore, how to avoid the agglomeration of nanomaterials and improve the dispersibility and compatibility of nanomaterials in the polyurethane matrix is ​​a key issue in nanomaterial modified polyurethane coatings. Summary of the invention

[0008] The purpose of the present invention is to provide a high-performance environmentally friendly coating and a galvanized sheet prepared therefrom in view of the above problems. The coating of the present invention has excellent mechanical properties, is easy to construct, and has weather resistance, and has broad application prospects.

[0009] The technical solution of the present invention is achieved in this way: A high-performance environmentally friendly coating comprises the following components in parts by weight: 120-150 parts of aqueous polyurethane dispersion, 10-15 parts of graphene oxide nanosheets, 4-10 parts of boron nitride nanosheets, 2-6 parts of inorganic nanoparticles, 0.5-2 parts of anti-settling agent, 0.5-2 parts of defoaming agent, 0.2-2 parts of wetting dispersant, and 50-100 parts of deionized water; the volume average particle size (D50) of the inorganic nanoparticles is 100-200nm.

[0010] Graphene oxide is a typical two-dimensional oxygen-containing graphene derivative with a large number of oxygen-containing functional groups, such as hydroxyl and epoxy groups at the bottom of the plane, and carbonyl groups at the edge. Compared with graphene, the oxygen-containing functional groups on the surface of graphene oxide are more reactive, giving it different properties from graphene. It has better water solubility, and the surface active groups can react with polyurethane or form hydrogen bonds, and have better compatibility with water-based polyurethane. Due to the presence of active groups, graphene oxide is easy to adhere to the surface of metal sheets, effectively inhibiting the oxidation behavior of the metal, and acting as a charge transfer barrier to block the occurrence of pitting. However, due to the presence of defects, the mechanical properties of graphene oxide are poor, which affects the mechanical properties of the coating. In order to improve the mechanical properties of the coating, the present invention adds a certain amount of boron nitride nanosheets and inorganic nanoparticles.

[0011] Boron nitride has the same honeycomb atomic structure as graphene, and has excellent dielectric properties and high-temperature oxidation resistance. Compared with graphene oxide, boron nitride nanosheets are cheap, have excellent thermal stability, thermal conductivity, electrical insulation and chemical stability, and can be used to improve the mechanical properties and friction resistance of polymer coatings, so that the coating will not be affected by galvanic corrosion. At the same time, since both boron nitride nanosheets and graphene oxide nanosheets have a lamellar structure, graphene oxide can improve the dispersion performance of the inert filler-boron nitride nanosheets, effectively solving the problem of poor compatibility between boron nitride nanosheets and the matrix, and improving its dispersion performance.

[0012] The surface of inorganic nanoparticles usually has hydroxyl groups in different states, which makes the surface deviate from its stable structure due to lack of oxygen, and has high activity. It can improve the hardness, density, thermal stability and chemical stability of the coating by bonding with certain groups in the polyurethane matrix. When the particle size of inorganic nanoparticles is too large, it is difficult to exert the size effect; at the same time, inorganic nanoparticles have high surface activity. When their particle size is too small, they are prone to agglomeration in the polymer solution. During use, attention should be paid to adjusting the particle size of inorganic nanoparticles. By selecting inorganic nanoparticles of a specific particle size, they can be dispersed between boron nitride nanosheets and graphene oxide nanosheets, playing a dispersing and lubricating role similar to that of bearings, improving the isolation and shielding effects of the nanosheet material, and improving the stability of the coating.

[0013] Furthermore, the solid content of the aqueous polyurethane dispersion is 50-70%. The type of aqueous polyurethane is not particularly limited, and it can be prepared by introducing a hydrophilic component in the process of preparing polyurethane. For example, after polyether diol and diisocyanate are reacted for a certain period of time, a hydrophilic chain extender (dimethylolbutyric acid, etc.) and an amine compound are added to continue the reaction to obtain a prepolymer, and then a small molecule diol is added to carry out a chain extension reaction to obtain an aqueous polyurethane dispersion.

[0014] Furthermore, a high-performance environmentally friendly coating comprises the following components in parts by weight: 120-150 parts of aqueous polyurethane dispersion, 10-15 parts of graphene oxide nanosheets, 6-8 parts of boron nitride nanosheets, 3-4.5 parts of inorganic nanoparticles, 0.5-2 parts of anti-settling agent, 0.5-2 parts of defoaming agent, 0.2-2 parts of wetting dispersant, and 50-100 parts of deionized water. By adjusting the amount of each component, the dispersion of the filler can be better promoted, which is conducive to forming a dense structure and improving the hardness and stability of the coating.

[0015] Furthermore, the mass ratio of the graphene oxide nanosheets, boron nitride nanosheets, and inorganic nanoparticles is 3:2:1. The nanosheet structure has a high aspect ratio. The lateral dimensions of the graphene oxide nanosheets and boron nitride nanosheets used in the present invention are not particularly limited, as long as they present a lamellar structure. Generally, the lateral dimensions of the graphene oxide nanosheets are 0.5-10μm; the lateral dimensions of the boron nitride nanosheets are 0.5-10μm. Furthermore, considering the dispersion and isolation effects, the lateral dimensions of the graphene oxide nanosheets are 1-3μm; the lateral dimensions of the boron nitride nanosheets are 1-3μm. Among them, the average lateral dimensions of the graphene oxide nanosheets used in the present invention are 2μm; and the average lateral dimensions of the boron nitride nanosheets are 1μm.

[0016] Furthermore, the inorganic nanoparticles are a mixture of one or more of nano-silicon dioxide, nano-titanium dioxide, nano-calcium carbonate, nano-zinc oxide, and nano-zirconium dioxide.

[0017] Furthermore, the anti-settling agent is a mixture of one or more of BYK420, BYK425 and BYK430.

[0018] Furthermore, the defoamer is a silicone defoamer or a mineral oil defoamer.

[0019] Furthermore, the wetting and dispersing agent is a mixture of one or more of polyacrylate sodium salt, polyacrylate ammonium salt, and polyphosphate.

[0020] Furthermore, the preparation method of the high-performance environmentally friendly coating comprises the following steps: S1. Weigh each component by weight; S2. After the graphene oxide nanosheets, boron nitride nanosheets, inorganic nanoparticles and deionized water are evenly mixed, an aqueous polyurethane dispersion is added, and the mixture is dispersed by stirring. Then, an anti-settling agent, a defoaming agent and a wetting dispersant are added, and the mixture is evenly mixed again to obtain a high-performance environmentally friendly coating.

[0021] Furthermore, the stirring and dispersing rate is 500-1000 r / min.

[0022] On the other hand, the present invention also provides a galvanized sheet, which is prepared by coating a high-performance environmentally friendly coating on the surface of the cleaned galvanized sheet.

[0023] Beneficial effects: The present invention uses graphene oxide nanosheets, boron nitride nanosheets and inorganic nanoparticles to modify waterborne polyurethane coatings. The oxygen-containing functional groups on the surface of graphene oxide are more reactive and have better compatibility with waterborne polyurethane. At the same time, due to the presence of active groups, graphene oxide is easy to adhere to the surface of metal plates, effectively inhibiting the oxidation behavior of metals. Boron nitride nanosheets are cheap and can be used to improve the mechanical properties and friction resistance of polymer coatings, so that the coating will not be affected by galvanic corrosion. At the same time, since both boron nitride nanosheets and graphene oxide nanosheets present a lamellar structure, graphene oxide can improve the dispersion performance of inert filler-boron nitride nanosheets, effectively solve the problem of poor compatibility between boron nitride nanosheets and substrates, and improve its dispersion performance. By selecting inorganic nanoparticles of specific particle size, they can be dispersed between boron nitride nanosheets and graphene oxide nanosheets, playing a dispersing and lubricating role similar to that of bearings, improving the isolation and shielding effects of nanosheet materials, and improving the stability of the coating. DETAILED DESCRIPTION

[0024] In order to better illustrate the purpose, technical solutions and advantages of the present application, the present application will be further described below in conjunction with specific examples. In the following examples and comparative examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0025] The graphene oxide nanosheets used in the following examples and comparative examples have an average lateral size of 2 μm; the boron nitride nanosheets have an average lateral size of 1 μm. The specific preparation processes of the following examples and comparative examples are as follows: S1. Weigh each component by weight; S2. After the graphene oxide nanosheets, boron nitride nanosheets, inorganic nanoparticles and deionized water are evenly mixed, an aqueous polyurethane dispersion is added, and the mixture is dispersed by stirring. Then, an anti-settling agent, a defoaming agent and a wetting dispersant are added, and the mixture is evenly mixed again to obtain a high-performance environmentally friendly coating; the stirring and dispersing rate is 700 r / min.

[0026] Example 1 A high-performance environmentally friendly coating comprises the following components in parts by weight: 120 parts of aqueous polyurethane dispersion, 10 parts of graphene oxide nanosheets, 6 parts of boron nitride nanosheets, 3 parts of inorganic nanoparticles, 0.5 parts of anti-settling agent, 0.5 parts of defoaming agent, 0.2 parts of wetting and dispersing agent, and 60 parts of deionized water; the volume average particle size of the inorganic nanoparticles is 100 nm; the solid content of the aqueous polyurethane dispersion is 60%; the inorganic nanoparticles are nano-silicon dioxide; the anti-settling agent is BYK420; the defoaming agent is polydimethylsiloxane; and the wetting and dispersing agent is sodium polyacrylate.

[0027] Example 2 A high-performance environmentally friendly coating comprises the following components in parts by weight: 150 parts of aqueous polyurethane dispersion, 15 parts of graphene oxide nanosheets, 8 parts of boron nitride nanosheets, 4.5 parts of inorganic nanoparticles, 2 parts of anti-settling agent, 2 parts of defoaming agent, 2 parts of wetting and dispersing agent, and 90 parts of deionized water; the volume average particle size of the inorganic nanoparticles is 200 nm; the solid content of the aqueous polyurethane dispersion is 60%; the inorganic nanoparticles are nano-silicon dioxide; the anti-settling agent is BYK425; the defoaming agent is polydimethylsiloxane; and the wetting and dispersing agent is ammonium polyacrylate.

[0028] Example 3 A high-performance environmentally friendly coating comprises the following components in parts by weight: 120 parts of aqueous polyurethane dispersion, 15 parts of graphene oxide nanosheets, 6 parts of boron nitride nanosheets, 4.5 parts of inorganic nanoparticles, 0.5 parts of anti-settling agent, 2 parts of defoaming agent, 0.2 parts of wetting and dispersing agent, and 90 parts of deionized water; the volume average particle size of the inorganic nanoparticles is 100 nm; the solid content of the aqueous polyurethane dispersion is 60%; the inorganic nanoparticles are nano-silicon dioxide; the anti-settling agent is BYK430; the defoaming agent is polydimethylsiloxane; and the wetting and dispersing agent is sodium polyacrylate.

[0029] Example 4 A high-performance environmentally friendly coating comprises the following components in parts by weight: 130 parts of aqueous polyurethane dispersion, 12 parts of graphene oxide nanosheets, 6.5 parts of boron nitride nanosheets, 3.5 parts of inorganic nanoparticles, 1 part of anti-settling agent, 1 part of defoaming agent, 1 part of wetting and dispersing agent, and 70 parts of deionized water; the volume average particle size of the inorganic nanoparticles is 130 nm; the solid content of the aqueous polyurethane dispersion is 60%; the inorganic nanoparticles are nano-silicon dioxide; the anti-settling agent is BYK420; the defoaming agent is polydimethylsiloxane; and the wetting and dispersing agent is ammonium polyacrylate.

[0030] Example 5 A high-performance environmentally friendly coating comprises the following components in parts by weight: 140 parts of aqueous polyurethane dispersion, 14 parts of graphene oxide nanosheets, 7.5 parts of boron nitride nanosheets, 4 parts of inorganic nanoparticles, 1.5 parts of anti-settling agent, 1.5 parts of defoaming agent, 1.5 parts of wetting and dispersing agent, and 80 parts of deionized water; the volume average particle size of the inorganic nanoparticles is 180 nm; the solid content of the aqueous polyurethane dispersion is 60%; the inorganic nanoparticles are nano-silicon dioxide; the anti-settling agent is BYK430; the defoaming agent is polydimethylsiloxane; and the wetting and dispersing agent is sodium polyacrylate.

[0031] Example 6 A high-performance environmentally friendly coating comprises the following components in parts by weight: 135 parts of aqueous polyurethane dispersion, 12 parts of graphene oxide nanosheets, 4 parts of boron nitride nanosheets, 4 parts of inorganic nanoparticles, 1 part of anti-settling agent, 1 part of defoaming agent, 1 part of wetting and dispersing agent, and 80 parts of deionized water; the volume average particle size of the inorganic nanoparticles is 150 nm; the solid content of the aqueous polyurethane dispersion is 60%; the inorganic nanoparticles are nano-silicon dioxide; the anti-settling agent is BYK420; the defoaming agent is polydimethylsiloxane; and the wetting and dispersing agent is sodium polyacrylate.

[0032] Example 7 A high-performance environmentally friendly coating comprises the following components in parts by weight: 135 parts of aqueous polyurethane dispersion, 12 parts of graphene oxide nanosheets, 10 parts of boron nitride nanosheets, 4 parts of inorganic nanoparticles, 1 part of anti-settling agent, 1 part of defoaming agent, 1 part of wetting and dispersing agent, and 80 parts of deionized water; the volume average particle size of the inorganic nanoparticles is 150 nm; the solid content of the aqueous polyurethane dispersion is 60%; the inorganic nanoparticles are nano-silicon dioxide; the anti-settling agent is BYK420; the defoaming agent is polydimethylsiloxane; and the wetting and dispersing agent is sodium polyacrylate.

[0033] Example 8 A high-performance environmentally friendly coating comprises the following components in parts by weight: 135 parts of aqueous polyurethane dispersion, 12 parts of graphene oxide nanosheets, 8 parts of boron nitride nanosheets, 2 parts of inorganic nanoparticles, 1 part of anti-settling agent, 1 part of defoaming agent, 1 part of wetting and dispersing agent, and 80 parts of deionized water; the volume average particle size of the inorganic nanoparticles is 150 nm; the solid content of the aqueous polyurethane dispersion is 60%; the inorganic nanoparticles are nano-silicon dioxide; the anti-settling agent is BYK420; the defoaming agent is polydimethylsiloxane; and the wetting and dispersing agent is sodium polyacrylate.

[0034] Example 9 A high-performance environmentally friendly coating comprises the following components in parts by weight: 135 parts of aqueous polyurethane dispersion, 12 parts of graphene oxide nanosheets, 8 parts of boron nitride nanosheets, 6 parts of inorganic nanoparticles, 1 part of anti-settling agent, 1 part of defoaming agent, 1 part of wetting and dispersing agent, and 80 parts of deionized water; the volume average particle size of the inorganic nanoparticles is 150 nm; the solid content of the aqueous polyurethane dispersion is 60%; the inorganic nanoparticles are nano-silicon dioxide; the anti-settling agent is BYK420; the defoaming agent is polydimethylsiloxane; and the wetting and dispersing agent is sodium polyacrylate.

[0035] Example 10 A high-performance environmentally friendly coating comprises the following components in parts by weight: 135 parts of aqueous polyurethane dispersion, 12.5 parts of graphene oxide nanosheets, 6.8 parts of boron nitride nanosheets, 3.6 parts of inorganic nanoparticles, 1.2 parts of anti-settling agent, 0.9 parts of defoaming agent, 1.1 parts of wetting and dispersing agent, and 75 parts of deionized water; the volume average particle size of the inorganic nanoparticles is 180 nm; the solid content of the aqueous polyurethane dispersion is 60%; the inorganic nanoparticles are nano-silicon dioxide; the anti-settling agent is BYK430; the defoaming agent is polydimethylsiloxane; and the wetting and dispersing agent is ammonium polyacrylate.

[0036] Embodiment 11 A high-performance environmentally friendly coating comprises the following components in parts by weight: 135 parts of aqueous polyurethane dispersion, 12 parts of graphene oxide nanosheets, 8 parts of boron nitride nanosheets, 4 parts of inorganic nanoparticles, 1 part of anti-settling agent, 1 part of defoaming agent, 1 part of wetting and dispersing agent, and 80 parts of deionized water; the volume average particle size of the inorganic nanoparticles is 150 nm; the solid content of the aqueous polyurethane dispersion is 60%; the inorganic nanoparticles are nano-silicon dioxide; the anti-settling agent is BYK420; the defoaming agent is polydimethylsiloxane; and the wetting and dispersing agent is sodium polyacrylate.

[0037] Comparative Example 1 A high-performance environmentally friendly coating comprises the following components in parts by weight: 135 parts of aqueous polyurethane dispersion, 0 parts of graphene oxide nanosheets, 16 parts of boron nitride nanosheets, 8 parts of inorganic nanoparticles, 1 part of anti-settling agent, 1 part of defoaming agent, 1 part of wetting and dispersing agent, and 80 parts of deionized water; the volume average particle size of the inorganic nanoparticles is 150 nm; the solid content of the aqueous polyurethane dispersion is 60%; the inorganic nanoparticles are nano-silicon dioxide; the anti-settling agent is BYK420; the defoaming agent is polydimethylsiloxane; and the wetting and dispersing agent is sodium polyacrylate.

[0038] Comparative Example 2 A high-performance environmentally friendly coating comprises the following components in parts by weight: 135 parts of aqueous polyurethane dispersion, 18 parts of graphene oxide nanosheets, 0 parts of boron nitride nanosheets, 6 parts of inorganic nanoparticles, 1 part of anti-settling agent, 1 part of defoaming agent, 1 part of wetting and dispersing agent, and 80 parts of deionized water; the volume average particle size of the inorganic nanoparticles is 150 nm; the solid content of the aqueous polyurethane dispersion is 60%; the inorganic nanoparticles are nano-silicon dioxide; the anti-settling agent is BYK420; the defoaming agent is polydimethylsiloxane; and the wetting and dispersing agent is sodium polyacrylate.

[0039] Comparative Example 3 A high-performance environmentally friendly coating comprises the following components in parts by weight: 135 parts of aqueous polyurethane dispersion, 14.4 parts of graphene oxide nanosheets, 9.6 parts of boron nitride nanosheets, 0 parts of inorganic nanoparticles, 1 part of anti-settling agent, 1 part of defoaming agent, 1 part of wetting and dispersing agent, and 80 parts of deionized water; the volume average particle size of the inorganic nanoparticles is 150 nm; the solid content of the aqueous polyurethane dispersion is 60%; the inorganic nanoparticles are nano-silicon dioxide; the anti-settling agent is BYK420; the defoaming agent is polydimethylsiloxane; and the wetting and dispersing agent is sodium polyacrylate.

[0040] Comparative Example 4 A high-performance environmentally friendly coating comprises the following components in parts by weight: 135 parts of aqueous polyurethane dispersion, 12 parts of graphene oxide nanosheets, 8 parts of boron nitride nanosheets, 4 parts of inorganic nanoparticles, 1 part of anti-settling agent, 1 part of defoaming agent, 1 part of wetting and dispersing agent, and 80 parts of deionized water; the volume average particle size of the inorganic nanoparticles is 40 nm; the solid content of the aqueous polyurethane dispersion is 60%; the inorganic nanoparticles are nano-silicon dioxide; the anti-settling agent is BYK420; the defoaming agent is polydimethylsiloxane; and the wetting and dispersing agent is sodium polyacrylate.

[0041] Comparative Example 5 A high-performance environmentally friendly coating comprises the following components in parts by weight: 135 parts of aqueous polyurethane dispersion, 12 parts of graphene oxide nanosheets, 8 parts of boron nitride nanosheets, 4 parts of inorganic nanoparticles, 1 part of anti-settling agent, 1 part of defoaming agent, 1 part of wetting and dispersing agent, and 80 parts of deionized water; the volume average particle size of the inorganic nanoparticles is 300 nm; the solid content of the aqueous polyurethane dispersion is 60%; the inorganic nanoparticles are nano-silicon dioxide; the anti-settling agent is BYK420; the defoaming agent is polydimethylsiloxane; and the wetting and dispersing agent is sodium polyacrylate.

[0042] The high-performance environmentally friendly coatings prepared in the examples and comparative examples were subjected to hardness test (GB / T 6739-2006), paint film adhesion test (GB / T 5210-2006), and salt spray resistance test (GB / T 1771-2007); the results are shown in Table 1.

[0043] As can be seen from the results of Table 1, the present invention uses graphene oxide nanosheets, boron nitride nanosheets and inorganic nanoparticles to modify waterborne polyurethane coatings. The oxygen-containing functional groups on the surface of graphene oxide are more reactive and have better compatibility with waterborne polyurethane. At the same time, due to the presence of active groups, graphene oxide is easy to adhere to the surface of the metal sheet, effectively inhibiting the metal oxidation behavior. At the same time, since both the boron nitride nanosheets and the graphene oxide nanosheets present a lamellar structure, graphene oxide can improve the dispersion performance of the inert filler-boron nitride nanosheets, effectively solving the problem of poor compatibility between the boron nitride nanosheets and the matrix, and improving its dispersion performance. By selecting inorganic nanoparticles of a specific particle size, it can be dispersed between the boron nitride nanosheets and the graphene oxide nanosheets, playing a dispersing and lubricating role similar to that of a bearing, improving the isolation and shielding effect of the nanosheet material, and improving the stability of the coating. Compared with Example 11, when Comparative Examples 1-3 lack graphene oxide nanosheets, boron nitride nanosheets and inorganic nanoparticles, a dispersion system of a specific form cannot be formed, affecting the coating performance. Comparative Examples 4-5 show that when the particle size of inorganic nanoparticles is too large, it is difficult to exert the size effect; at the same time, inorganic nanoparticles have high surface activity, and when their particle size is too small, they are prone to agglomeration in the polymer solution. During use, care should be taken to adjust the particle size of the inorganic nanoparticles.

[0044] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A high-performance environmentally friendly coating, characterized in that: Contains the following components in parts by weight: 120-150 parts of aqueous polyurethane dispersion, 10-15 parts of graphene oxide nanosheets, 4-10 parts of boron nitride nanosheets, 2-6 parts of inorganic nanoparticles, 0.5-2 parts of anti-settling agent, 0.5-2 parts of defoaming agent, 0.2-2 parts of wetting dispersant, and 50-100 parts of deionized water; the volume average particle size of the inorganic nanoparticles is 100-200nm.

2. A high-performance environmentally friendly coating as claimed in claim 1, characterized in that: The solid content of the aqueous polyurethane dispersion is 50-70%.

3. A high-performance environmentally friendly coating as claimed in claim 1, characterized in that: The mass ratio of the graphene oxide nanosheets, the boron nitride nanosheets and the inorganic nanoparticles is 3:2:

1.

4. A high-performance environmentally friendly coating as claimed in claim 1, characterized in that: The inorganic nanoparticles are a mixture of one or more of nano silicon dioxide, nano titanium dioxide, nano calcium carbonate, nano zinc oxide and nano zirconium dioxide.

5. A high-performance environmentally friendly coating as claimed in claim 1, characterized in that: The anti-settling agent is a mixture of one or more of BYK420, BYK425 and BYK430.

6. A high-performance environmentally friendly coating as claimed in claim 1, characterized in that: The defoamer is an organosilicon defoamer or a mineral oil defoamer.

7. A high performance environmentally friendly coating as claimed in claim 1, characterized in that: The wetting and dispersing agent is a mixture of one or more of polyacrylic acid sodium salt, polyacrylic acid ammonium salt and polyphosphate.

8. A high performance environmentally friendly coating as claimed in claim 1, characterized in that: The preparation method of the high-performance environmentally friendly coating comprises the following steps: S1. Weigh each component by weight; S2. After the graphene oxide nanosheets, boron nitride nanosheets, inorganic nanoparticles and deionized water are evenly mixed, an aqueous polyurethane dispersion is added, and the mixture is dispersed by stirring. Then, an anti-settling agent, a defoaming agent and a wetting dispersant are added, and the mixture is evenly mixed again to obtain a high-performance environmentally friendly coating.

9. A high performance environmentally friendly coating as claimed in claim 8, characterized in that: The stirring and dispersing rate is 500-1000 r / min.

10. A galvanized sheet, characterized in that: The high-performance environmentally friendly coating according to any one of claims 1 to 9 is applied on the surface of a cleaned galvanized sheet to obtain the coating.

Citation Information

Patent Citations

  • Water-based graphene acrylic acid-polysiloxane coating and preparation method thereof

    CN111777910A

  • Water-based paint

    CN114286845A

  • Graphene nano composite material modified heavy anti-corrosion coating and preparation method thereof

    CN116515372A

  • Nanosheet compositions and their use in lubricants and polishing slurries

    US20180079989A1

  • Electrochemically stable elastomer-encapsulated particles of anode active materials for lithium batteries and methods of producing

    WO2019173581A1

Cited By

  • Preparation process of environment-friendly film coating

    CN120441894A

  • High-performance coating and color steel plate prepared from high-performance coating

    CN120554941A

  • High-performance coating and color steel plate prepared thereby

    CN120554941B

  • Boron nitride modified waterborne polyurethane coating with high mechanical property and preparation method thereof

    CN120648348A